Study on cultivation of the anaerobic microbial consortium BKM capable of methane fermentation under seawater conditions - Thi Thu Hong, Do; Thu Hoai, Nguyen; Thi Viet Ha, Bui; Thuy Hang, Dinh (VNU Journal of Science: Natural Sciences and Technology, 2017)
Marine environment in Vietnam has been severely polluted due to daily discharge of untreated organic wastes from land. Meanwhile, anaerobic digestion, the most efficient technology for the treatment of organic wastes is commonly uneffective in marine environment, the main reason is the lack of microorganisms capable of adapting to this special environment. In the present study, we showed an effective method to cultivate the marine microbial consortium BKM capable of performing the process of anaerobic digestion of organic wastes under seawater conditions. A complex substrate derived from 5-day fermented 10% rice bran in synthetic seawater, that had pH of 4.5, COD ~ 45000 mg O 2 /L, VFA ~ 900 mg/L was developed to apply as substrate for the cultivation procedure. Anaerobic synthetic seawater medium containing 10% of the fermented rice bran has been proven effective in cultivation of the BKM consortium and allowed to reach a stable specific methane production activity of 180 mL CH 4 /g COD after 5 days at 28 - 30°C. The 15 day well-grown culture of BKM contained 2.8´10 9 MPN/ml methanogens, mainly belonged to hydrogenotrophic Methanomicrobiales and acetoclastic Methanosarcinales, as showed by analyses of mcrA gene library. In a 2 liter laboratory bioreactor model containing poultry manure mixed in seawater, the BKM culture showed highly effective, enabling the methane production to start after just 3 days of incubation, reaching 80% COD elimination after 60 days. The preliminary results indicated that BKM consortium cultivated in seawater medium with fermented 10% rice bran as showed in this study would have high application potential in anaerobic organic waste treatment systems operating under seawater condition.